Biosynthesis of Fosfomycin by Streptomyces fradiae - Rogers, Thomas O. (1974)
The antibiotic fosfomycin was produced as a secondary metabolite in a glucose-asparagine medium containing citrate, l-methionine, and l-glutamate. The citrate requirement for antibiotic synthesis was related to its requirement for growth. In contrast, l-methionine and l-glutamate caused a marked stimulation of fosfomycin production and had no effect on growth. l-Methionine had to be added early to effect maximal antibiotic synthesis later in the fermentation. The l-glutamate requirement was not specific, since several tricarboxylic acid cycle intermediates could replace this amino acid. l-Asparagine was the most effective nitrogen source for growth and production of fosfomycin. Glycine, an alternate nitrogen source, supported fosfomycin synthesis only when added in excess of that needed for growth. Cobalt and inorganic phosphate were required also for antibiotic production at concentrations exceeding those supporting maximal growth. Radioactive incorporation studies showed that the methyl carbon of methionine was the precursor of the methyl of fosfomycin. Carbon 1 of fosfomycin was derived from glucose carbons 1 and 6, whereas glucose-2-(14)C labeled fosfomycin carbon 2. Radioactivity from acetate-2-(14)C was distributed equally between fosfomycin carbons 1 and 2. No incorporation of acetate-1-(14)C, asparagine-U-(14)C, citrate-1,5-(14)C, or glutamate-U-(14)C occurred. The labeling pattern of fosfomycin carbons 1 and 2 was similar to that found in 2-aminoethylphosphonate from Tetrahymena.